Actitud intercultural en la metodología docente del primer grado de secundaria en las Instituciones Educativas Miguel Grau de Padre Cocha y Sagrado Corazón de Iquitos 2023 - Panduro Panduro, Licier Marilu (2024)
The main objective of this study was to determine the level of intercultural attitude among communication area teachers of the first grade of secondary education at the Miguel Grau de Padre Cocha and Sagrado Corazón de Iquitos Educational Institutions - 2023. The research was comparative in nature with a contemporary field and univariable design. The population consisted of 48 teachers from the selected educational institutions, who also constituted the sample. To collect the data, a validated survey was used to evaluate intercultural attitude in three dimensions: cognitive, affective, and attitudinal. The results showed that 49.3% of the teachers had a regular level of intercultural attitude, 46.4% demonstrated good acceptance, and the remaining 4.3% had poor acceptance. In the cognitive dimension, 64.6% of the teachers reached a regular level of acceptance, while in the affective dimension, 54.2% also were at a regular level. Lastly, in the attitudinal dimension, 87.5% of the teachers showed good acceptance. These findings suggest that while the majority of teachers have an acceptable intercultural attitude, there is still room to improve these attitudes through the implementation of innovative pedagogical strategies. Adopting such strategies could foster a more inclusive and respectful environment for cultural diversity, benefiting both teachers and students.